Optimalisasi Peran Masjid dalam Pendidikan Anak Perspektif Makro dan Mikro - Ikhwan, Afiful (EDUKASI: Jurnal Pendidikan Islam, 2013)
The mosque as a instrument that can be used to prostrate, also means it can be used for social activities involving human dimension by making it as a central activity. This relates also to the potential mosque itself should be empowered with all the ability of the managers. In this case it takes expertise (skills) are not only sufficient, but must be fully implemented as the implementation of the propaganda bi ahsan al-amal (make changes by mobilizing all abilities). With this kind of understanding, the mosque can be interpreted as an instrument or means of universal worship. Not only worship mahdhoh (micro), but also worship ghayro mahdhah (macro). So, mosques back again in his role as the time of Prophet Muhammad saw- before that, as an educational center that seeks to educate the religion of Islam and its values, to become ones way of life.